Pengaruh Kualitas Produk Kopi Terhadap Kepuasan Konsumen: Studi kasus pada kedai kopi “Dari Hati” di Kota Makassar - Rosada, Ida; Nurliani , N; Husain, Tsalis Kurniawan; Khaerudin, Taufik (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
A coffee shop (cafe) offers a relaxed atmosphere for fast food and drink. A good cafe can provide satisfaction for consumers in terms of service, affordable products and prices, and adequate equipment and facilities. The research objectives are: (1) Describe the coffee drink production process and (2) Describe product quality. (3) Describe consumer satisfaction with the quality of coffee drink products. (4) Analyzing the influence of coffee drink product quality on consumer satisfaction. The population of this research is consumers who make purchases directly at the